2010
DOI: 10.1093/treephys/tpq066
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression pattern in response to wounding, methyl jasmonate and ethylene in the bark of Hevea brasiliensis

Abstract: Natural rubber production in Hevea brasiliensis is determined by both tapping and ethephon frequencies. It is affected by a complex physiological disorder called tapping panel dryness. This syndrome is likely to be induced by environmental and latex harvesting stresses. Defence responses, including rubber biosynthesis, are dramatically mediated by wounding, jasmonate and ethylene (ET), among other factors. Using real-time RT-PCR, the effects of wounding, methyl jasmonate (MeJA) and ET on the relative transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 54 publications
0
66
0
2
Order By: Relevance
“…In previous research, 18S and ACTIN genes have been the most widely used reference genes for expression normalization in rubber tree (Dusotoit-Coucaud et al, 2009;Duan et al, 2010;Li et al, 2010;Tang et al, 2010). However, extensive analysis is not conducted to validate their suitability as reference genes in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, 18S and ACTIN genes have been the most widely used reference genes for expression normalization in rubber tree (Dusotoit-Coucaud et al, 2009;Duan et al, 2010;Li et al, 2010;Tang et al, 2010). However, extensive analysis is not conducted to validate their suitability as reference genes in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…We have ever characterized HbCOI1 and HbJAZ1 in laticifer cells, which are related to COI1 and AtJAZ1/AtJAZ2 from Arabidopsis, respectively (Peng et al, 2009;Tian et al, 2010). The expression of HbCOI1 is up-regulated in latex of laticifers (Peng et al, 2009) while down-regulated in bark tissues by methyl jasmonate (Duan et al, 2010), suggesting that JA-responsiveness is diverse between different tissues of rubber trees. However, ethrel has little effect on the expression of HbCOI1 both in latex and in bark tissues (Peng et al, 2009;Duan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of HbCOI1 is up-regulated in latex of laticifers (Peng et al, 2009) while down-regulated in bark tissues by methyl jasmonate (Duan et al, 2010), suggesting that JA-responsiveness is diverse between different tissues of rubber trees. However, ethrel has little effect on the expression of HbCOI1 both in latex and in bark tissues (Peng et al, 2009;Duan et al, 2010). Transcription pattern analysis also reveals that HbJAZ1 is strongly up-regulated by tapping and mechanical wounding in latex, but not by ethrel application (Tian et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This early induction HbETR2 was suppressed by an ethylene inhibitor, 1-MCP. In this work, Duan et al (2010) have shown the effect of ethylene and wounding treatments on the downstream-response genes of ethylene signalling pathway. Thus, it opened the perspective of crosstalk signalling between phytohormones in Hevea brasiliensis.…”
Section: Characterization Of the Ethylene Biosynthesis And Signallingmentioning
confidence: 98%
“…The molecular actors involved in ethylene perception and signalling were also studied in Hevea brasiliensis (Duan et al, 2010). Two genes of ethylene perception, Hevea brasiliensis Ethylene Receptor 2 (HbETR2) and Hevea brasiliensis Ethylene-insensitive 2 (HbEIN2), and a gene of ethylene signalling (HbEIN3) were differentially regulated by ethylene treatment.…”
Section: Characterization Of the Ethylene Biosynthesis And Signallingmentioning
confidence: 99%